2016
DOI: 10.17795/ijpbs-5132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Computer-Assisted Cognitive Remediation on Improving Cognitive Functions in Patients with Schizophrenia: A Before-After Study

Abstract: Background: Cognitive impairment is a chronic and disabling manifestation of schizophrenia. Objectives: This before-after study was conducted to examine the effect of a short course computer-assisted cognitive remediation on improving cognitive functions of patients with schizophrenia. Materials and Methods: Twenty patients with schizophrenia were enrolled into the study. The intervention consisted of 10 onehour sessions held 2-3 times a week, using the Cogpack software that includes tasks to improve attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(7 reference statements)
1
2
0
Order By: Relevance
“…In fact, these elements were also defended and described by the contributions of Toribio-Guzmán [2]. In the same sense we see connections with other similar works carried out in different countries [4,8,[16][17][18][19][20][21][22][23][24][25]. Specifically, we understand that cognitive stimulation using software can be more effective than traditional cognitive stimulation, especially while it is maintained [5].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In fact, these elements were also defended and described by the contributions of Toribio-Guzmán [2]. In the same sense we see connections with other similar works carried out in different countries [4,8,[16][17][18][19][20][21][22][23][24][25]. Specifically, we understand that cognitive stimulation using software can be more effective than traditional cognitive stimulation, especially while it is maintained [5].…”
Section: Discussionsupporting
confidence: 71%
“…Gradior Spain [2] Smart brain Spain [4] Serius Games (SG) [16] Virtual Reality (VR) India [8] Erica Italy [17] JCORES Japan [18] Cogpack Iran [19] Constant Therapy USA [20] Parrot [21] Long Lasting Memories (LLM) Spain [22] BBA Spain [23] REHACOP Spain [24] COMCOG Corea [25] In the same way, other recent studies have demonstrated the efficacy of video games in improving cognitive processes affected by the physiological effect of aging, neurodegenerative diseases or others, with potentially beneficial effects. The Pervasive game for personalized treatment of cognitive and functional deficits associated with chronic and Neurodegenerative diseases (PERSON project) proposed new tools for cognitive rehabilitation, with the aim of improving the quality of life of patients with cognitive deficits, especially in the early stages, through the use of sophisticated and non-invasive technology [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large body of literature has consistently demonstrated the benefits of long-term CRT on cognition and psychosocial functioning with moderate effect sizes ( Katsumi, Hoshino, Fujimoto, & Niwa, 2015 ; McGurk, Twamley, Sitzer, McHugo, & Mueser, 2007 ; Grynszpan et al, 2011 ; Deste et al, 2019 ; Kurtz & Richardson, 2011 ). In 2016, a before-after study was conducted in Iran by Sharifi and associates ( Sharifi, Sedighnia, Ataie, Tabatabaee, & Tehranidoost, 2016 ). This study demonstrated the efficacy of CRT in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%